Profitability Ratios And Influence Earning Per Share (EPS) on Stock Price On Food and Beverage Companies Go Public In the Indonesia Stock Exchange - Anggara, Stefanus Wahyu; Isafaatun, SE., MM, Eliya; Nawarcono, SE., MM, Winanto (Accounting, 2010)
The development of stock prices in the capital market is an important indicator for studying the behavior of the market, namely investors. To determine whether investors will be trading in the stock market, usually will base its decisions on the various instruments available in the public and private. The data is meaningful or valuable to the investor if the data is causing make transactions on the capital market, where transactions are reflected through share price. Financial Accounting Standards (PSAK, 2007 No. 3) states that with the increasing number of companies that sell securities in the capital markets, interim financial statements become increasingly necessary. The main aspect of the interim financial reports issued by companies that report was not audited. This will cause significant problems regarding the reliability of investment decision makers. To increase the level of the company´s financial performance, we need a ratio analysis method that aims to analyze the financial position of an enterprise. Ratios used to determine the ability of firms to obtain profits in relation to sales, total assets, investment and own capital. Profitability ratios include return on assets (ROA), Return On Equity (ROE), and Pofit Net Margin (NPM). EPS is used to measure the success of management in achieving profitability for the company owner. Value of ROA, ROE, NPM, and EPS increasing it will increase shareholder confidence in the company. but each Chapter are interconnected and support each other, so that by the end of the Chapter will be obtained a conclusion of the problem. Thesis writers are interested in selecting food and beverage companies as an object of research in writing this essay to analyze the increasing needs of everyday people. Based on a discussion of profitability ratios and EPS to the stock price on 10 food and beverage companies go public in Indonesia Stock Exchange (IDX) then it can be deduced results of research conducted on 10 companies from 15 food and beverage companies that went public and listed on the Stock Exchange Indonesia (BEI) that the profitability ratio has fluctuated over the 2007-2009 period with Earning Per Share (EPS) during the 2007-2009 period amounted to USD. 1229.95. Keywords: Capital Market, Stock Exchange, Go Public